2016
DOI: 10.1115/1.4032680
|View full text |Cite
|
Sign up to set email alerts
|

Markov Nonlinear System Estimation for Engine Performance Tracking

Abstract: This paper presents a joint state and parameter estimation method for aircraft engine performance degradation tracking. Contrast to previously reported techniques on state estimation that view parameters in the state evolution model as constants, the method presented in this paper treats parameters as time-varying variables to account for varying degradation rates at different stages of engine operation. Transition of degradation stages and estimation of parameters are performed by particle filtering (PF) unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Recently, LSTMs have also been investigated in conjunction with model-based techniques, such as particle filters (PF), in order to alleviate the limitation of insufficient observations for degradation model parameter estimation. PFs have been widely studied for the prognosis of complex engineering systems such as HVAC [125] and aircraft engines [126] in which the degradation model can be continuously fine-tuned by the incoming sensing observations based on Bayesian inference. In Ref.…”
Section: Analyzing Degradation Patternsmentioning
confidence: 99%
“…Recently, LSTMs have also been investigated in conjunction with model-based techniques, such as particle filters (PF), in order to alleviate the limitation of insufficient observations for degradation model parameter estimation. PFs have been widely studied for the prognosis of complex engineering systems such as HVAC [125] and aircraft engines [126] in which the degradation model can be continuously fine-tuned by the incoming sensing observations based on Bayesian inference. In Ref.…”
Section: Analyzing Degradation Patternsmentioning
confidence: 99%
“…The GPA method, one of the common performance-based condition monitoring methods, is a cost-efficient approach to representing the degradation as the deviation of measurements [21][22][23]. There are three key issues that need to be investigated in the GPA method [24]: (i) nonlinear tracking: studies have shown that the degradation curve of gas turbine performance is nonlinear, including the polynomial term [25], the logarithmic term [26], and the exponential term [27]. (ii) Health parameters: the health parameters should represent the health status of the gas turbine and are independent of the environmental factors or control factors that are not related to the degradation degree [28].…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature pertaining to RUL prediction for aircraft engines can be classified into two categories: model-based and data-driven prognostics [3][4][5]. Model-based prognostic methods describe system behavior and system degradation using physics-based models typically in combination with state estimators such as the Kalman filter, the particle filter, and the hidden Markov model [6]. While model-based prognostic methods provide closed-form solutions, certain assumptions must be made.…”
Section: Introductionmentioning
confidence: 99%